2011
DOI: 10.1111/j.1746-1049.2011.00128.x
|View full text |Cite
|
Sign up to set email alerts
|

ON THE PATH TO ECONOMIC GROWTH, DO REMITTANCES HELP? EVIDENCE FROM PANEL VARs

Abstract: Despite the emergence of remittances studies, knowledge about their effect on economic development is still ambiguous. This paper investigates the impact of remittances at macroeconomic level in developing countries controlling for endogeneity problems with the use of panel vector autoregression (panel VAR). The findings suggest that remittances have a positive, albeit small, impact on economic growth even without considering the role of institutions. When institutions are included, the pattern of response rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
1
14
0
1
Order By: Relevance
“…For example, some studies (Giuliano & RuizArranz, 2009;Helen& Robert, 2007) argued that international remittances can positively contribute to economic growth in developing countries in the absence of a properly functioning credit market. In a similar study, Zuniga (2011) has pointed out that the positive relation between remittances and economic growth while the impact may vary with geographical distributions of remittance receiving countries. However, Ahamada & Coulibaly (2013) found no causal relationship between remittances and economic growth in Sub-Saharan countries.…”
Section: Review Of Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…For example, some studies (Giuliano & RuizArranz, 2009;Helen& Robert, 2007) argued that international remittances can positively contribute to economic growth in developing countries in the absence of a properly functioning credit market. In a similar study, Zuniga (2011) has pointed out that the positive relation between remittances and economic growth while the impact may vary with geographical distributions of remittance receiving countries. However, Ahamada & Coulibaly (2013) found no causal relationship between remittances and economic growth in Sub-Saharan countries.…”
Section: Review Of Literaturementioning
confidence: 94%
“…Several other studies (see, for example, Bugamelli & Paterno, 2009, 2011Chami, Hakura & Montiel, 2009) examined the impact of remittances on output growth (GDP per capita) stabilisation in developing countries and found positive effects. Anzoateguiet al (2014) and Demirgüç-Kunt et al (2011) found that remittances can strengthen the financial development of the recipient country and can be used to meet its needs during negative income shocks (Osili 2007).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Given the magnitude of these flows, recent works on remittances have sought to determine their macroeconomic impact. Several studies focusing on the impact of remittances on growth (Zuniga 2011;Tansel and Yaşar 2010;Jayaraman, Choong, and Kumar 2010;Chami, Cosimano, and Montiel 2008), the real exchange rate (Beja 2011;Amuedo-Dorantes and Pozo 2004), economic volatility (Ahamada and Coulibaly 2011;Craigwell, Jackman, and Moore 2010;Jackman, Craigwell, and Moore 2009), and labor (Drinkwater, Levine, and Lotti 2009;Jadotte 2009;Airola 2008;Bussolo and Medvedev 2008;Amuedo-Dorantes and Pozo 2006) have surfaced. In this study, the focus is on the latter, that is, the labor market impact of remittances.…”
Section: Introductionmentioning
confidence: 99%
“…They undisputedly represent an important channel of levelling unemployment, increasing welfare, and play an important role in assessing economic impacts of international migration on sending and receiving countries (see e.g. Cruz Zuniga ; Massey et al . ).…”
Section: Introductionmentioning
confidence: 99%